Case report: Left ventricular perforation caused by right ventricular pacemaker lead - Huang, Xiang; Zhou, Heng; Li, Xiao-Mei; Li, Xiao-Lan (Frontiers in Cardiovascular Medicine, 2023)
Background: Right ventricular (RV) lead perforation through interventricular septum and left ventricular (LV) free wall is an extremely rare and potential life-threatening complication. In this case report, we described a rare case of LV perforation caused by a RV pacing lead and the management of this complication. Case Summary: A 92-year-old man was admitted due to complete atrioventricular block. We performed a dual-chamber pacemaker implantation, but pacing failure occurred on the second postoperative day (POD). Thoracic computed tomography scan showed that RV lead perforated through both the interventricular septum and LV free wall. A transvenous lead extraction of the penetrating lead was performed uneventfully and RV lead was re-fixed at the lower right ventricular septum on the 5th POD. Discussion: Identification of high-risk patients is mandatory to prevent this serious complication, and transvenous lead extraction with surgical back-up can be feasible.